ANALYSIS OF THE SUCCESS OF MOBILE BANKING (M-BANKING) AND DELONE AND MCLEAN MODEL ON BCA'S MAIN BRANCH OFFICE (KCU) DIPONEGORO SURABAYA - Huda, Muchlis Alkhoiruli; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
BCA is the bank that provides the best experience of its facitlity, one of their facility is mobile banking for their customers, it is called m-BCA, stands for mobile BCA. There are many features on m-BCA, like m-Admin, m-Transfer, m-Payment, m-Commerce, m-Info, and cash withdrawl. Until 2011, the users of m-BCA reached 2.3 million users that take advanteges from it (detikFinance , 2011). The problem is m-BCA now has so many complaints from its users, like errors often occurred on the system and less user friendly. There are also users that encountered problem when it comes to try to login on m-BCA (detikFinance, 2014). Based on the problem and with analysing the successness of mobile banking m-BCA using DeLone and McLean model (2003), it composed by System Quality, Information Quality, Service Quality, Usability, User Satisfaction, and Net Benefit. The Data used in this case is primary data that obtained from questionnaire which was filled by 125 respondents. Then the data is analysed with descriptive analysing to understand the successness of m-BCA and SEM analysing to understand the factors which are affected the successness of m-BCA. The results of this research show that the positive effect of variable Quality System against user satisfaction. System Quality variables have positive influence against the use of. The variable quality of the positive effect of the use of the service. To increase the success of m-BCA then it should improve the quality of Information on m-BCA that will have an impact on user satisfaction so as to achieve kebermanfaatan NET that can enhance the success of m-BCA. Recommendations for m-BCA, namely: 1) to the quality of the system should preferably be developed more flexibility the system so that it can be reached from anywhere, 2) to the quality of service should be improved security.